Teaching English Based-Realia for Young Learners in MBS (Muhammadiyah Boarding School) Mataram NTB - Humaira, Humaira; Bafadal, Fauzi; Isnaini, Isnaini (Universitas Muhammadiyah Mataram, 2023)
Essentially, language professionals have offered a plenty of fascinating and enjoyable language education approaches and ideas. Media realia is one of the alternative strategies presented in this study. The purpose of this research is to investigate the impact of using realia media to teach English to young children. The study was conducted at the Sang Surya Muhammadiyah Boarding School Kindergarten in Mataram with 11 children as the sample. The pre-experimental approach, namely pre-test and post-test group design was applied in this research. The instruments to gather the data were observation, a vocabulary test and recording, while the data collection procedure was done through pre-test, treatment and post test. Finally, the data were analyzed using a pre-experimental formula in the form of statistical computation. The result shows that the comparison of the t-test and t-table is 3.21 ≥ 2.60, or the test results exceed the minimal accomplishment levels. It revealed that the use of the